Phytochemistry and cytotoxic activity of Annona muricata Seed Extracts against MEF cell line - Saja Nabhan Addai; Bahir Abdul Razzaq Mshimesh; Ayad Mohammad Rasheed (College of Pharmacy / Mustansiriyah University, 2022)
Until February 2017, about two hundred and twelve bioactive compounds were confirmed to be present in Annona muricata. Annonaceous acetogenins (AGEs) are the predominant compounds that present in A.muricata followed by phenols, alkaloids and other compounds.   Leaves and seeds were the main parts examined in medical field. This study was conducted to evaluate the most probable active chemical components of Annona muricata seeds extracts.  Cytotoxic activity of Annona muricata seed extracts against MEF (mice embryo fibroblast) cell line was evaluated by 3-(4, 5 dimethythiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay. Ethanol and chloroform extracts were added at a final concentration (1.56, 3.12, 6.25, 12.5, 25, 50 and 100 μg/ml) for 72h exposure to MEF cells. The applications of common identification and characterization techniques which were Fourier-Transform Infrared (FT-IR) and gas chromatography-mass spectroscopy (GC-MS) for analysis of bioactive compounds in the crude plant extracts involved. As conclusion, Annona muricata seed extract have a marked anti-proliferative activity against MEF cell line after 72h exposure period in concentration-dependent manner. The major active constituents of A.muricata seeds extract involve acetogenins, flavonoids, and alkaloids.